Sudanese medical students’ satisfaction with online learning and its association with their psychological distress: a cross-sectional study - Muhannad Bushra Masaad Ahmed; Ahmed Balla M. Ahmed; Moram Elfadel Abdelrhaman Gasmalha; Olla Zuhair Elamin Abdalla; Safinat Hassan Mohammed Ahmed; Blsam Abdelmoneam Ahmed Mohammed; Rabaa Alamein Omer Ebrahim; Maab Hisham Saeed Abdeen; Esraa Obeid Mohammed Babiker; Tasneem Abdelgader Abdelrhman Ahmed; Alkhansa Ahmed Osman Ahmed; Doaa Salaheldin Mohamed Ahmed; et al. (BMC Medical Education)
Abstract Background Online learning has emerged as an alternative to continuing higher education during the ongoing conflict in Sudan. Despite its numerous benefits, online learning is often associated with challenges like stress, anxiety, and depression. Satisfaction plays a pivotal role in shaping students’ perceptions of online education quality and their mental well-being, especially under adverse conditions like conflict. Hence, this study aimed to evaluate the satisfaction of Sudanese medical students with online learning and its association with psychological distress issues, including anxiety, depression, and stress, during the current Sudan war. Methods A cross-sectional study was conducted among Sudanese medical students who transitioned to online learning during the conflict. Satisfaction with online learning was assessed using a validated questionnaire consisting of eight dimensions, while depression symptoms were measured with the Patient Health Questionnaire-9, anxiety with the Generalized Anxiety Disorder-7, and perceived stress with the Perceived Stress Scale-10. Associations between demographic factors and key outcomes were analyzed using independent t-tests, chi-square tests, and one-way ANOVA, with statistical significance set at p < 0.05. Results Among the 1,891 medical students surveyed, the mean satisfaction score for online learning was 26.2 out of 40. Mild to moderate depression was reported by 59.4% of students, while 62% experienced mild to moderate anxiety, and 21% reported high stress levels. Lower satisfaction was significantly associated with higher levels of depression, anxiety, and stress (all p < 0.001). Conclusion Sudanese medical students reported positive satisfaction with online learning during the conflict, yet this was accompanied by high levels of depression, anxiety, and stress. These findings highlight the need for integrated mental health support and improved digital access to enhance online education. Addressing these challenges is essential to ensuring student well-being and sustaining quality education in conflict settings. Further research across different settings can help develop more effective interventions.